MONITORING KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN HIPERTENSI DI PUSKESMAS TLOGOSARI KULON KOTA SEMARANG - Fef Rukminingsih (Jurnal Farmasi IKIFA, 2023)
Type 2 diabetes mellitus (T2DM) is a metabolic disease characterized by hyperglycemia. T2DM is a risk factor for hypertension. T2DM patients with hypertension who have uncontrolled blood glucose levels can cause more serious complications. This study aims to determine blood sugar levels in T2DM patients with hypertension at the Tlogosari Kulon Health Center, Semarang City. This research is a descriptive observational study. Data collection uses purposive sampling technique. The data used is medical record data of T2DM patients with hypertension at the Tlogosari Kulon Health Center, Semarang City for the period September 2022 - February 2023. The inclusion criteria for this study are patients who are ≥ 45 years old, have the results of checking fasting blood sugar levels (FBSL) for 2 consecutive months. Incomplete data will be excluded. The results showed that of the 40 T2DM patients with hypertension, there were 26 female patients and 14 male patients. Most patients were aged 60-69 years, namely 22 people. A total of 30 patients used oral hypoglycemic drugs for less than 5 years. A total of 31 patients (77.5%) received combination therapy with metformin and glimepiride. A total of 12 patients (30%) had fasting blood sugar levels in accordance with the therapy target.